Genus Phyllanthus: Traditional uses and Biological activities - Ruba Joujeh; Dima Joujeh (Zagazig Journal of Pharmaceutical Sciences)
Medicinal plants represent essential elements of traditional medicine. They have been used to treat various ailments. Phyllanthus (Euphorbiaceae) is a large genus, includes important medicinal plants. It has about 1000 plant species, comprising trees, shrubs and herbs. Phyllanthus species are known globally for their medicinal uses and are used in the treatment of many diseases. It has been estimated that more than 500 chemical constituents have been obtained from species of this genus. The medicinal value of different plant parts is proven scientifically. The extracts prepared from Phyllanthus plants displayed anti-cancer, anti-inflammatory, anti-diabetic, anti-oxidant, anti-bacterial, nephroprotective, hepatoprotective, immunomodulatory effects. Phyllanthus species have been the focus of many biological and phytochemical studies in recent years, due to their wide distribution. This review emphasizes the importance of Phyllanthus plants, showing their traditional uses and and scientifically proven biological effects to open the door to take advantage of them in medicine and industry.